Paroxysmal Nocturnal Hemoglobinuria with a Distinct Molecular Signature Diagnosed Ten Years after Allogenic Bone Marrow Transplantation for Acute Myeloid Leukemia - Alberto Santagostino; Laura Lombardi; Gerard Dine; Pierre Hirsch; Srimanta Chandra Misra (Case Reports in Hematology)
Paroxysmal nocturnal hemoglobinurea (PNH) is a rare disorder of complement regulation due to somatic mutation of PIGA (phosphatidylinositol glycan anchor) gene. We herewith report a case who developed a symptomatic PNH long after an allogenic marrow transplant. Some reasonable arguments concerning the origin of PNH clone have been discussed. The molecular studies revealed presence of JAK2 and TET2 mutations without a BCOR mutation. The literature review has been performed to probe into the complex interplay of autoimmunity and clonal selection and expansion of PNH cells, which occurs early in hematopoietic differentiation. The consequent events such as hypoplastic and/or hemato-oncologic features could further be explained on the basis of next-generation sequencing (NGS) studies. Paroxysmal nocturnal hemoglobinuria (PNH) is a rare clonal disorder of hematopoietic stem cells, characterized by a somatic mutation of the phosphatidylinositol glycan-class A (PIGA). The PIGA gene products are crucial for biosynthesis of glycosylphosphatidylinositol (GPI) anchors, which attaches a number of proteins to the plasma membrane of the cell. Amongst these proteins, the CD55 and CD59 are complement regulatory proteins. The CD55 inhibits C3 convertase whereas the CD59 blocks the membrane attack complex (MAC) by inhibiting the incorporation of C9 to MAC. The loss of complement regulatory protein renders the red cell susceptible to complement-mediated lysis leading to intravascular and extravascular hemolysis. The intravascular hemolysis explains most of the morbid clinical manifestations of the disease. The clinical features of syndrome of PNH are recurrent hemolytic episodes, thrombosis, smooth muscle dystonia, and bone marrow failure; other important complications include renal failure, myelodysplastic syndrome (MDS), and acute myeloid leukemia (AML). The most used therapies were blood transfusions, immunosuppressive, and steroid. Allogeneic stem cell transplantation was also practiced. At present, the therapy of choice is eculizumab (Soliris, Alexion Pharmaceuticals), a humanized monoclonal antibody that blocks activation of the terminal complement at C5. The limiting factor for this therapy is breakthrough hemolysis and the frequent dosing schedule. Ravulizumab (ALXN1210) is the second generation terminal compliment inhibitor which seems to provide a sustained control of hemolysis without breakthrough hemolysis and with a longer dosing interval.